The effects of watershed disturbances on dissolved organic carbon dynamics of a stream - Meyer, Judy L.; Tate, Cathy M.
The response of a stream ecosystem to disturbance in its watershed was investigated by comparing mass balances of dissolved organic carbon (DOC) for a stream draining an undisturbed watershed with a stream draining a watershed that was clear?cut 2 yr before the study began. These second?order streams are in Coweeta Hydrologic Laboratory, North Carolina. Both streams had similar, elevated DOC concentrations (from <1 to 5 mg/L) during storms. Rising and falling limbs of the hydrograph also had similar DOC concentrations. During the growing season DOC concentration increased from headwater seep to the weir in the undisturbed stream under baseflow conditions. No significant longitudinal change was observed in the stream draining the clear?cut watershed. Hence concentration was consistently lower in baseflow samples during the growing season in the stream draining the clear?cut watershed. As a result annual DOC export from the clear?cut watershed was less (9.8?11.5 kg/ha) than from the reference watershed (14.6?15.1 kg/ha). The lower DOC export was partly due to reduced DOC inputs from throughfall and leaching of fresh litter, but most importantly to lower DOC inputs in subsurface water and probably also less in?stream generation of DOC. The rate of recovery of this stream form disturbance is therefore dependent on the rate at which the terrestrial system recovers.